Optimizing Plant Spacing and Mulching for Enhanced Weed Control and Cucumber Yield (Cucumis sativus) under Varied Sowing Conditions - Orji, Janeth Oliver; Nwufo, Martin Ikechukwu; Onyewuchi, Oyibo Patricia; Duruigbo, Cyril Ifeanyi; Ikeh, Angus Onwudiwe; Nze, Edward Onuawuchi; Amanze, Alice Nnenna (Applied Research in Science and Technology, 2026)
Background: Weeds pose a significant challenge to crop farming, particularly in cucumber production in Nigeria. They compete with cucumber plants for essential resources such as water, nutrients, and sunlight, which can lead to reduced crop yields. They harbor insects and disease organisms, serve as alternate host to pests, and compete with crops for nutrients, moisture, light, and space. Weeds cause damage to crops, reduce the yield and quality by competing with the crops, and cause harm to animals that feed on them. The production of cucumber has increased in Nigeria due to its importance, but it is still in short supply because of poor yield, which could be attributed to weed infestation.Aims: This study was conducted to investigate the impact of spacing and mulching on weed control and fruit quality of cucumber (Cucumis sativus) at various sowing dates in humid ecology.Methods: The experiment was carried out using a split-split plot arrangement layout in a Randomized Complete Block Design. The treatments consisted of three factors (time of planting, spacing, and mulching). The main plot was sowing dates (April, May, June, July, August and September), the sub plot was spacing (20cm x 50cm, 40cm x 50cm and 60cm x 50cm), sub-sub plot was mulching (no mulch, black plastic mulch, transparent plastic mulch, wood shaving) all were replicated 3 times. Result: The sowing date had a significant effect (p<0.05) on weed dry weight at 4 and 6 weeks after emergence. Sowing in April recorded the lowest weed dry weight (0.31g at 4 WAE and 0.79g at 6 WAE) in 2015 and (3.84g at 4 WAE; 3.16g at 6 WAE) in 2016. Cucumbers that were spaced at 20 cm x 50 cm recorded the lowest weed dry weight (8.53g at 4WAE and 4.60g at 6WAE) in 2015 and also in 2016 (10.36g at 4WAE and 5.33g at 6WAE). Black polythene recorded the lowest weed dry weight (2.87g at 4WAE; 1.79g at 6WAE) in 2015 and (2.95g at 4WAE and 1.88g at 6WAE) in 2016. Conclusion: The study revealed that effective weed control and high fruit quality were achieved by sowing early in April and May at closer spacing, combined with black polythene mulching. These practices recorded the lowest weed dry weight, while early sowing also produced better fruit quality. Therefore, the study recommends sowing early in April and May at closer spacing and using black polythene mulch for optimal cucumber production